The Effect of Social Responsibility on the Competitiveness of Business Organizations (A Field Study in the Branch of the Arab Academy for Science, Technology and Maritime Transport in Lattakia) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to study the impact of social responsibility in its dimensions (educational level - human level - administrative level) on the competitiveness of the branch of Arab Academy for Science, Technology and Maritime Transport in Lattakia. The researcher relied on the analytical descriptive approach, and used the comprehensive inventory method for the study population by distributing (62) questionnaires to the scientific and administrative employees in the studied university, since they were fully retrieved and analyzed, to test the hypotheses of the study, the researcher used the Student T test for one sample, as well as the analysis of Linear regression. The research found a decrease in both the educational and human level of social responsibility, and a rise in the administrative level, the results also revealed a decrease in the level of competitiveness in the studied university. The research also found that there is a significant impact of the dimensions of social responsibility (the educational dimension - the human dimension - the administrative dimension) on competitiveness, and therefore a positive impact of social responsibility on improving competitiveness. The research concluded with a set of recommendations related to the need to improve competitiveness in the labor market through optimal utilization of available resources, as well as introducing the employees of the academy to the dimensions of social responsibility and taking care of all its aspects, in addition to identifying the needs of members of the local community and working to meet them.